Job re-grading, real wages, and the cycle - Robert A. Hart; J. Elizabeth Roberts (Institute for the Study of Labor (IZA), 2011)
This paper makes use of the British New Earnings Survey Panel Dataset between 1976 and 2010. It consists of individual-level payroll data and comprises a random sample of 1% of the entire male and female labor force. About two-thirds of within- and between-company moves involve job re-grading (measured at 3-digit occupation level) while one-third of movers retain their job titles. We find that the real wages of both male and female workers who change job titles within companies are significantly more procyclical than job stayers. This lends support to the predicted procyclical real wage effects of the Reynolds-Reder-Hall job re-grading hypothesis. On the extensive margin, title changers and title retainers who move jobs between companies exhibit the same degrees of wage cyclicality and these are considerably greater than for job stayers.
urn:nbn:de:101:1-20110927152
Keywords: E32; J31; 330; real wage cyclicality; spot wages; job moves; job re-grading